Kink Solutions for a Class of Generalized Dissipative Equations - Marianna Ruggieri (Abstract and Applied Analysis)
We study, in this paper, a generalized viscoelastic equation which includes several interesting models considered in some recent papers. Many physically important nonlinear PDEs can be reduced to nonlinear ODEs by means of reduction techniques. So it is significant and very interesting to study, among all the closed-form solutions admitted by the model, the corresponding kink waves. A plot of the obtained solution is performed.